On certain subclasses of univalent functions associated with generalized Poisson distribution series - Porwal, S.; Ghai, S.K. (Carpathian Mathematical Publications, 2025)
The purpose of the present paper is to obtain necessary and sufficient condition for generalized Poisson distribution series to be in certain classes of univalent functions. We also consider an integral operator associated with generalized Poisson distribution series.